New insights into posttranslational modifications of Hippo pathway in carcinogenesis and therapeutics. Issue 1 (March 2016) - He, Mingjing; Zhou, Zhuan; Shah, Anil; Hong, Yang; Chen, Qianming; Wan, Yong
Abstract PTMs (posttranslational modifications) such as ubiquitylation, sumoylation, acetylation and protein methylation are pivotal modifiers that determine the activation, deactivation or subcellular localization of signaling proteins, facilitating the initiation, amplification and transduction of signaling. Accumulating evidence suggest that several key signaling molecules in Hippo signaling pathway are tightly regulated by various types of PTMs. Malfunction of these critical signaling modules such as YAP/TAZ, MAT1/2 and LATS1/2 due to deregulated PTMs has been linked to a variety of human diseases such as cancer. In this review article, we summarized the current understanding of the impact of PTMs in regulating Hippo signaling pathway and further discussed the potential therapeutic intervention from the view of PTMs and Hippo pathway.